Finance and Development, December 1975. (Finance and Development; Finance and Development ;, 1975)
This paper reviews the 1975 Annual Meetings of the Boards of Governors of the IMF and the World Bank that were held in Washington, D.C., from September 1-5. The paper highlights that three separate but related themes dominated the discussion at the Annual Meetings. The first was the need to combat recession without aggravating inflation. The second was the immediate needs of developing countries in the present situation. And the third was the urgency of making further progress toward reform of the international monetary system.